A Randomized Control Trial on the Effects of MoBeGo, a Self-Monitoring App for Challenging Behavior. (November 2022) - Bruhn, Allison; Wehby, Joseph; Hoffman, Lesa; Estrapala, Sara; Rila, Ashley; Hancock, Eleanor; Van Camp, Alyssa; Sheaffer, Amanda; Copeland, Bailey
The purpose of this study was to examine the effects of MoBeGo, a mobile self-monitoring app, on the initial and sustained academic engagement and disruptive behavior of third- to eighth-grade students with challenging behavior. Student–teacher pairs ( N = 57) were randomly assigned to the treatment (MoBeGo) or control (business-as-usual) condition. We conducted systematic direct observation of students' behavior throughout prebaseline, baseline, intervention, and postintervention conditions of the study. Multivariate multilevel models revealed differential improvement for the MoBeGo group in student outcomes (less disruptive behavior; more academic engagement) from baseline to intervention, as well as successful postintervention effects for disruptive behavior. Limitations, future directions, and implications for practice are discussed.